Dysregulated Responsiveness of Circulating Dendritic Cells to Toll-Like Receptors in ANCA-Associated Vasculitis - Braudeau, Cécile; Néel, Antoine; Amouriaux, Karine; Martin, Jérôme C.; Rimbert, Marie; Besançon, Audrey; Giraudet, Stéphanie; Terrien, Caroline; Aliaga, Marine; Salabert-Le Guen, Nina; Hémont, Caroline; Hamidou, Mohamed; et al. (Frontiers in Immunology, 2017)
Objective: Dendritic cells (DCs) are critical effectors of innate and adaptive immunity playing crucial roles in autoimmune responses. We previously showed that blood DC numbers were reduced in autoimmune ANCA-associated vasculitis (AAV). Here, we assessed toll-like receptor (TLR) responsiveness of blood DCs from patients with granulomatosis with polyangiitis (GPA) or microscopic polyangiitis (MPA). Methods: Blood samples from healthy controls (HC), GPA or MPA patients, without treatment, during acute phase (AP) or remission (RP) were analyzed. Cytokine production by DCs and T cells was assessed on whole blood by flow cytometry after TLRs or polyclonal stimulation, respectively. Results: We first showed that GPA and MPA are associated with a decreased blood DC number during AP. Conventional DCs (cDCs) from patients with GPA and MPA in AP exhibited a profound decrease of IL-12/IL-23p40 production after TLR3, 4 or 7/8 stimulation compared to patients in remission and HC, with a return to normal values in RP. TNFα secretion was also affected, with a decrease in cDCs from GPA patients in AP after TLR3 stimulation but an increase after TLR7/8 stimulation. In contrast, the responsiveness of pDCs to TLR7 and 9 was only marginally affected. Finally, we observed that IFNγ-producing CD4+ T cell frequency was significantly lower in AP-GPA patients than in HC. Conclusion: We describe, for the first time, a dysregulated response to TLRs of circulating DCs in AAV patients mostly affecting cDCs that exhibit an unexpected reduced inflammatory cytokine secretion possibly contributing to an altered Th cell response.